2022
DOI: 10.1186/s13213-022-01664-w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and safety assessment of Bacillus strains isolated from Burkinabe traditional condiment “soumbala”

Abstract: Purpose Alkaline-fermented foods (AFFs) play an essential role in the diet of millions of Africans particularly in the fight against hidden hunger. Among AFFs, soumbala is a very popular condiment in Burkina Faso, available and affordable, rich in macronutrients (proteins, lipids, carbohydrates, essential amino acids, and fatty acids), micronutriments (minerals, B group vitamins), and fibers. Bacillus spp. are known to be the predominant microbial species in AFFs and thus have elicited enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…No hemolytic properties were observed. The hemolytic activities of Bacillus [Dabiré et al, 2022], Chryseobacterium [Sud et al, 2020], Mycobacterium [Augenstreich et al, 2020], and Stenotrophomonas genera [Peters et al, 2020] were reported. However, only Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…No hemolytic properties were observed. The hemolytic activities of Bacillus [Dabiré et al, 2022], Chryseobacterium [Sud et al, 2020], Mycobacterium [Augenstreich et al, 2020], and Stenotrophomonas genera [Peters et al, 2020] were reported. However, only Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Of these seven papers, four did not deal with safety concerns related to QPS TUs. Three papers had problems related to the identification methodology used (Bae et al., 2022 ; Dabire et al., 2022 ; Yeak et al., 2022 ) and/or source attribution (Aly et al., 2022 ; Bae et al., 2022 ; Dorsch et al., 2022 ). The paper of Bae et al.…”
Section: Assessmentmentioning
confidence: 99%
“…Bacteraemia was diagnosed in a highly immunocompromised patient suffering from gut dysbiosis with a B. subtillis strain also present in fermented soya (natto), which was consumed daily by the patient (Kato et al., 2022 ). Haemolytic activity was discovered in some B. amyloliquefaciens (Dabire et al., 2022 ; Gauri et al., 2022 ) and B. subtilis (Dabire et al., 2022 ) strains; a property which is covered by the qualification ‘absence of toxigenic activity’ for Bacillus spp.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…are reported to be the most important species involved in the fermentation of several indigenous African fermented condiments. These include soumbala , iru , daddawa and ogiri using raw materials such as locust beans and melon seeds [ [8] , [9] , [10] ]. The biochemical activities of Bacillus during fermentation are also responsible for the acceptable organoleptic characteristics such as taste, flavour, visual appearance, and texture [ 11 , 12 ] associated with these foods.…”
Section: Introductionmentioning
confidence: 99%